Aplikasi ZPT Giberelin dan Teknik Pemangkasan Buah Untuk Meningkatkan Pertumbuhan dan Produksi Tanaman Semangka (Citrullus vulgaris Schard.) di sela Tanaman Kelapa Sawit - Nadiya Pirhat; Anis Tatik Maryani; Heri Junedi (Jurnal Media Pertanian, 2023)
Watermelon is one of the horticultural commodities in the fruit group which is quite attractive to the people of Indonesia, especially people in the lowland areas. Besides that, the lowlands are known for their fertile soil characteristics so that people can easily cultivate crops. However, there are still problems faced by farmers in planting watermelons, one of which is the few varieties of watermelon plants that can meet the quality of the fruit according to market demand in certain areas. This can be done with several efforts, namely pruning the fruit and giving Plant Growth Regulator(PGR). In addition, farmers can also optimize agricultural land by planting watermelons between annual crops such as immature oil palm (TBM).This research was carried out experimentally in the form of a factorial experiment arranged in a randomized block design (RBD) consisting of 2 factors, namely the first factor with 4 gibberellin application treatments (0 ml l-1; 3 ml l-1; 5 ml l-1 and 7 ml l-1) and the second factor with 4 pruning treatments (without pruning; leaving 1 fruit/plant; leaving 2 fruits/plant and leaving 3 fruits/plant), each treatment was repeated 3 times. The results showed that giving gibberellin concentrations of 7 ml l-1 and pruning the fruit leaving 1 fruit per plant gave the highest yields for each parameter observed both in quantity and quality for growth and production of watermelon plants. Farmers can optimize oil palm land so that it helps the economy during immature oil palm plantations (TBM).